Dos palmeras adventicias en la flora argentina - Delucchi, Gustavo (2000)
In this paper two adventive palms are reported to the Flora of Argentina: Phoenix Canariensis Chabaud and Trachycarpus fortunei (Hook.) H. Wendl. They grown in anthropic places of urban and suburban regions of the provinces of Buenos Aires, Santiago del Estero and Tucumán. A description of this species and the causes determining its naturalisation are given.